Semiotic Analysis of Sephora’s Beauty Campaign Video - Josephine Valencia Chan (Institute of Research and Community Outreach - Petra Christian University, 2022)
Social campaign has gained its popularity over these past years. With the rapid business development, many brands compete with each other to create a simple campaign video but still has a meaningful story. To analyze the data, the writer use semiotic approach. This study aims to discover the meaning of verbal and visual signs, and in what ways those meanings are conveyed in Sephora’s The Unlimited Power of Beauty video. The findings show that in The Unlimited Power of Beauty video, Sephora strives to redefine the term of beauty which cannot be determined merely by particular criteria such as having a white and flawless skin, but beauty can be defined in all forms, sizes, and ages through the verbal and visual signs.